Commented translation of Heisenberg's paper, “On the reinterpretation of kinematic and mechanical relations in quantum theory” - Fabris, Júlio César; Piattella , Oliver Fabio (Cadernos de Astronomia, 2025)
We present the translation of the article published by Werner Heisenberg in 1925, which constitutes a landmark in the development of quantum mechanics. Some  introductory comments are presented, followed by the Portuguese version of the text originally written in German.
Keywords: quantum mechanics; Werner Heisenberg; international year of quantum mechanics